The breast cancer conservative treatment. Cosmetic results – BCCT.core – Software for objective assessment of esthetic outcome in breast cancer conservative treatment: A narrative review. Issue 126 (April 2016) - Cardoso, Maria João; Cardoso, Jaime Santos; Oliveira, Hélder P.; Gouveia, Pedro
Highlights: The BCCT.core is a computer program used for the esthetic evaluation of breast cancer conservative treatment. The BCCT.core software has been used by centres worldwide for clinical use and research. Several publications have confirmed its easiness of use and reproduciblity. Abstract: Background and objective: Cosmetic outcome of breast cancer conservative treatment (BCCT) remains without a standard evaluation method. Subjective methods, in spite of their low reproducibility, continue to be the most frequently used. Objective methods, although more reproducible, seem unable to translate all the subtleties involved in cosmetic outcome. The breast cancer conservative treatment cosmetic results (BCCT.core) software was developed in 2007 to try to overcome these pitfalls. The software is a semi-automatic objective tool that evaluates asymmetry, color differences and scar visibility using patient's digital pictures. The purpose of this work is to review the use of the BCCT.core software since its availability in 2007 and to put forward future developments. Methods: All the online requests for BCCT.core use were registered from June 2007 to December 2014. For each request the department, city and country as well as user intention (clinical use/research or both) were questioned. A literature search was performed in Medline, Google Scholar and ISI Web of Knowledge for all publications using and citing "BCCT.core". Results: During this period 102 centers have requested the software essentially for clinical use. The BCCT.core software was used in 19 full published papers and in 29 conference abstracts. Conclusions: The BCCT.core is a user friendly semi-automatic method for the objective evaluation of BCCT. The number of online requests and publications have been steadily increasing turning this computer program into the most frequently used tool for the objective cosmetic evaluation of BCCT.